Analisis Faktor Risiko Kesehatan Ligkungan Dengan Kejadian Diare Pada Balita Di Wilayah Kerja Puskesmas Tanon 1 Kabupaten Sragen Tahun 2015-2020 - Munawaroh, Dinni Asmini; Sulistiyani, Sulistiyani; Darundiati, Yusniar Hanani (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2024)
Diarrhea disease is ranked second as the most common cause of death in children under five, both preventable and treatable. Diarrhea in the children under five group is the most vulnerable group and can result in death if not treated seriously. The highest incidence of diarrhea cases occurs in the first two years of life and will decrease as the child gets older. The purpose of this study was to determine the risk factors for the occurrence of diarrhea in toddlers in the working area of the Tanon 1 Public Health Center, Sragen Regency in 2015-2020. This type of research is analytic by design cross sectional. Secondary data in this study arecase children under five diarrhea, environmental sanitation factors, food sanitation factors and social economic factors. The data analysis used was univariate and bivariate with the chi square test α = 0.05. The results of the study show that there is a relationship between latrine management in 2015 (p-value=0.001) in 2016 (p-value=0.007) in 2017 (p-value= 0.032), there is a relationship between waste management (p-value=0,048) and cleanliness of food equipment in 2016 (p-value= 0.021), there is a relationship with clean water sources (p-value=0.049) and food management in 2017 (p-value= 0.003), there is a relationship with the condition of the floor of the house in 2019 (p-value= 0.49) with the incidence of diarrhea in children under five at the Tanon 1 Public Health Center, Sragen Regency.